2005
DOI: 10.1111/j.1471-4159.2004.02990.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducers of oxidative stress block ciliary neurotrophic factor activation of Jak/STAT signaling in neurons

Abstract: Generation of reactive oxygen species (ROS) with the accumulation of oxidative damage has been implicated in neurodegenerative disease and in the degradation of nervous system function with age. Here we report that ROS inhibit the activity of ciliary neurotrophic factor (CNTF) in nerve cells. Treatment with hydrogen peroxide (H 2 O 2 ) as a generator of ROS inhibited CNTF-mediated Jak/STAT signaling in all cultured nerve cells tested, including chick ciliary ganglion neurons, chick neural retina, HMN-1 motor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 75 publications
4
67
0
Order By: Relevance
“…A site-directed mutagenesis experiment revealed that cysteine residues, Cys866 and Cys917, act as a redox-sensitive switch controlling the catalytic activity of Jak2 (29). However, there are inconsistencies regarding changes in Jak2 activity under oxidized conditions in previous reports (30,31). Research has suggested that Jak2 activity in response to oxidative stress may also be dependent on the cell line used, due to difference in structural elements of Jak2 (29).…”
Section: Discussionmentioning
confidence: 95%
“…A site-directed mutagenesis experiment revealed that cysteine residues, Cys866 and Cys917, act as a redox-sensitive switch controlling the catalytic activity of Jak2 (29). However, there are inconsistencies regarding changes in Jak2 activity under oxidized conditions in previous reports (30,31). Research has suggested that Jak2 activity in response to oxidative stress may also be dependent on the cell line used, due to difference in structural elements of Jak2 (29).…”
Section: Discussionmentioning
confidence: 95%
“…Both LIF and ciliary neurotrophic factor (CNTF) are members of the Il-6 cytokine family, they are structurally related and share common receptor component subunits [62]. CNTF has neuroprotective properties but cannot prevent oxidative damage in cells exposed to H 2 O 2 [63]. Thus LIF may be effective in controlling damage by in vitro ROS inducers.…”
Section: Reduced Apoptosis Correlated To Reduction In Caspases and Rosmentioning
confidence: 99%
“…3D). Because ROS generation blocks STAT3 signaling (23,33,34) and garcinol was found to induce ROS production in CAL27 cells, we next determined whether MTG, a well-known ROS scavenger, could restore the inhibitory effect of garcinol on STAT3 activation. For this, CAL27 cells were pretreated with 10 mmol/L antioxidant MTG for 120 minutes and were then subjected to 120-minute incubation with 25 mmol/L garcinol.…”
Section: Garcinol-induced Inhibition Of Stat3 Activation Is Ros-depenmentioning
confidence: 99%